2022
DOI: 10.1037/pas0001117
|View full text |Cite
|
Sign up to set email alerts
|

Dysphoria and well-being in daily life: Development and validation of ecological momentary assessment scales.

Abstract: Assessment of internalizing symptoms has generally relied on cross-sectional and retrospective self-reports, but ecological momentary assessment (EMA) is increasingly used to capture quick fluctuations in symptoms, enhance ecological validity, and improve recall accuracy. However, there are very few measures of internalizing symptoms that have been validated for use in EMA designs. In Study 1, we chose candidate items for EMA short forms of the Dysphoria and Well-Being scales from the Inventory of Depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Although PANAS-X items are very frequently used in EMA/AA research, there are alternative measures of affect and mood that are widely used in EMA studies (e.g., items from the Profile of Mood States or the Inventory of Anxiety and Depression Symptoms; Jimenez et al, 2022). Our findings do not provide information about other measures of affect (or other combinations of PANAS-X items), and the multilevel reliability of these measures needs to be evaluated in each study (see Jimenez et al, 2022). Indeed, the PANAS-X may not capture the full range of discrete affect states that a researcher may be interested in examining.…”
Section: Discussionmentioning
confidence: 99%
“…Although PANAS-X items are very frequently used in EMA/AA research, there are alternative measures of affect and mood that are widely used in EMA studies (e.g., items from the Profile of Mood States or the Inventory of Anxiety and Depression Symptoms; Jimenez et al, 2022). Our findings do not provide information about other measures of affect (or other combinations of PANAS-X items), and the multilevel reliability of these measures needs to be evaluated in each study (see Jimenez et al, 2022). Indeed, the PANAS-X may not capture the full range of discrete affect states that a researcher may be interested in examining.…”
Section: Discussionmentioning
confidence: 99%
“…The IDAS-II is a self-report measure that assesses symptoms over the past 2 weeks, with each item rated on a 5-point scale from 1 ( not at all ) to 5 ( extremely ). We focused on the General Depression subscale (20 items; α = .94); additionally, Dysphoria (10 items; α = .92) and Well-Being subscales (eight items; reverse-coded to reflect anhedonia; α = .89) were included to index affective symptoms of high negative affect and low positive affect, respectively (Jimenez et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…They also found that a large proportion of the variance (50%) in emotional awareness was accounted for by state scores, whereas trait scores were found to explain only 2%. Another study by Jimenez et al (2022) addressed the need for psychometrically robust EMA measures which capture both distress and anhedonia. The brief Dysphoria and Well-Being EMA measures were adapted from the Inventory of Depression and Anxiety Symptoms and validated by conducting principal factor analyses and internal consistency analyses on aggregated cross-sectional datasets (N = 8876).…”
Section: Introductionmentioning
confidence: 99%
“…The brief Dysphoria and Well-Being EMA measures were adapted from the Inventory of Depression and Anxiety Symptoms and validated by conducting principal factor analyses and internal consistency analyses on aggregated cross-sectional datasets (N = 8876). The two EMA scales were further evaluated in an EMA design among 279 college students at the within-and betweenperson levels, with results indicating that both scales showed acceptable to good internal consistency, strong criterion validity, and generally adequate discriminant validity (Jimenez et al, 2022). Besides this, Forkmann et al (2018) evaluated the psychometric properties of an item set for the assessment of suicidal ideation (i.e., passive and active suicidal ideation) and relevant proximal risk factors (e.g., anxiety, depression).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation